Challenges for Teaching Injury Prevention in a Juvenile Detention Center. Issue 1 (2nd January 2017) - Reed, Consuelo; Sheehan, Mary; Chapman, Rebekah; Keen, Jason; Divola, Susan; Buckley, Lisa
ABSTRACT: This case study explored the injury related experiences and perceptions of youth in detention and the delivery of first aid education in youth detention contexts. It aimed to develop an understanding of how a mainstream injury prevention intervention could be modified for youth detention populations. Teacher and student reactions to the program were examined and injury checklists, focus groups, and staff interviews were conducted. Analysis revealed serious injuries related to criminal behaviors, violence, dangerous driving, and substance use. Recommendations for youth detention interventions include lesson flexibility, discussions, role-plays, visual materials, peer support strategies, student-teacher relationships, and positive reinforcement.